Upaya Meningkatkan Kemampuan Motorik Kasar Anak Melalui Permainan Lompat Tali - Latifah Asma’ul Ashari; Tuti Hayati; Heri Hidayat (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study was motivated by the phenomenon that children's gross motor skills are not optimal, especially the strength and balance components in children. This can be seen when children do activities jumping from the table and jumping from one tile to another, there are still some children who are not good at jumping, some children are still hesitant and have difficulty jumping from the table so that children still have to be assisted by the teacher because the child is not able to maintain body balance after jumping. The purpose of this study was to determine: 1) Children's gross motor skills before the rope jumping game was implemented; 2) The process of implementing the rope jumping game to improve children's gross motor skills in each cycle; and 3) Children's gross motor skills after the rope jumping game was implemented in Group A RA El-Hurriyah 03 Cikarang Utara Bekasi throughout the cycle. This study is based on the idea that rope jumping games can improve children's gross motor skills. So the hypothesis proposed is that through the rope jumping game, it is suspected that children's gross motor skills in Group A at RA EL-Hurriyah 03 Cikarang Utara Bekasi can increase. The method used is classroom action research consisting of two cycles and each cycle includes four repeated stages, namely: planning, implementation, observation, and reflection. The data collection technique was obtained through interviews, observations, and documentation. The respondents were Group A at RA EL-Hurriyah 03 Cikarang Utara Bekasi as many as 10 children. The results of the study showed that the gross motor skills of children before the rope jumping game was implemented obtained an average value of 64 with sufficient criteria. The percentage of teacher activity showed an increase, namely in cycle I of 71% and with good criteria, and in cycle II of 96% with very good criteria. Likewise, children's activities showed an increase in each cycle. Cycle I was 64% with sufficient criteria. and cycle II the percentage was 96% with very good criteria. Children's Gross Motor Skills after the rope jumping game was implemented in Group A RA El-Hurriyah Cikarang Utara in all cycles experienced a significant increase. Cycle I obtained an average value of 71 with good criteria. While cycle II obtained an average value of 95 with very good criteria. Thus the proposed hypothesis is accepted, meaning that the rope jumping game is proven to be able to improve children's gross motor skills in Group A RA-El-Hurriyah 03 North Cikarang.